Opportunities and risks of diagnostic lab-on-a-chip systems in healthcare from a health system stakeholder's perspective. (May 2014) - Hoffmann, Wolfgang; Kuecuekbalaban, Pinar; Schumann, Maika; Kraft, Kathleen; Gebauer, Alexander; Muehlan, Holger; Schmidt, Silke
Aim: The aim of personalized medicine is to respond to the needs of individuals with appropriate treatment. Lab-on-a-chip systems (LOCs) can help to individualize therapeutic algorithms at the point of care. Herein, we discuss the perspectives, demands and concerns associated with LOCs.Methods: Interviews with 30 experts in the field of personalized medicine were conducted, addressing the requirements, potentials and risks of LOCs. The interviews were transcribed and evaluated by means of qualitative content analysis.Results: The majority of experts emphasize a considerable potential for the lab-on-a-chip industry with the largest potential in the context of point-of-care diagnostics. The direct-to-costumer use is regarded as risky, in particular with respect to the reliability of the results.Conclusion: In addition to a major potential of the implementation of LOCs, their impact on delivery of healthcare have to be considered, and early communication between physicians and LOC developers and manufacturers have to be ensured.